2021
DOI: 10.1097/iop.0000000000001785
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of 3 Strategies of Orbital Tumor Volume Measurement Using Phantom Modeling

Abstract: Purpose: The reliability of 3 volume measurement strategies was investigated using MRI and a simple method for creating phantom orbit tumors. Methods: Water-based starch was molded into orbital “tumors” of 3 shapes (sphere, ovoid, diffuse); water displacement was used to calculate volume. “Tumors” were placed into 3D-printed orbit phantoms, MRIs were obtained and volume analysis was performed. Observers measured tumor volume using ellipsoid volume (EV),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…Despite advances in computerized volumetric segmentation software and the use of high-resolution MRI, a prior study demonstrated that reliable assessment of infiltrative tumor growth is achieved only after a 25% increase in tumor size. 20 In our cohort, recurrence requiring secondary intervention was defined by sensitive neuro-ophthalmologic parameters and greater than 20% radiographic regrowth or a new region of tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…Despite advances in computerized volumetric segmentation software and the use of high-resolution MRI, a prior study demonstrated that reliable assessment of infiltrative tumor growth is achieved only after a 25% increase in tumor size. 20 In our cohort, recurrence requiring secondary intervention was defined by sensitive neuro-ophthalmologic parameters and greater than 20% radiographic regrowth or a new region of tumor growth.…”
Section: Discussionmentioning
confidence: 99%